Eliminating the Detrimental Effect of Secondary Doping on PEDOT : PSS Hole Transporting Material Performance. Issue 21 (29th September 2021) - Li, Yuda; Li, Qi; Wang, Xunchang; Fu, Qingyao; Hu, Ci; Qiu, Xianliang; Li, Tianjin; Wang, Feng
Abstract: Secondary doping has a long history of use in conductivity enhancement in poly(3, 4‐ethylenedioxythiophene) : poly(styrene sulfonate) (PEDOT : PSS). However, very little research has addressed its detrimental effect on application performance of PEDOT : PSS in organic solar cells. Herein, it was shown that the uneven drying of secondary dopant‐water mixture results in a nonuniform/continuous film structure, causing severe damage to the device efficiencies (dropping about 8 and 23 % for poly[(2, 6‐(4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)‐benzo[1, 2‐b:4, 5‐b']dithiophene))‐alt‐(5, 5‐(1', 3'‐di‐2‐thienyl‐5', 7'‐bis(2‐ethylhexyl)benzo[1', 2'‐c:4', 5'‐c']dithiophene‐4, 8‐dione))] (PBDB‐T) : 3, 9‐bis(2‐methylene‐(3‐(1, 1‐dicyanomethylene)‐indanone))‐5, 5, 11, 11‐tetrakis(4‐hexylphenyl)‐dithieno[2, 3‐d:2', 3'‐d']‐s‐indaceno[1, 2‐b:5, 6‐b']dithiophene (ITIC) and poly[(2, 6‐(4, 8‐bis(5‐(2‐ethylhexyl)‐4‐fluorothiophen‐2‐yl)benzo[1, 2‐b:4, 5‐b′]dithio‐phene))‐co‐(1, 3‐di(5‐thiophene‐2‐yl)‐5, 7‐bis(2‐ethylhexyl)‐benzo[1, 2‐c:4, 5‐c′]dithiophene‐4, 8‐dione))](PM6) : (3, 9‐bis(1‐oxo‐2‐methylene‐3‐(1, 1‐dicyanomethylene)‐5, 6‐difluoroindanone)‐5, 5, 11, 11‐tetrakis(4‐n‐hexylphenyl)‐dithieno[2, 3d:2′, 3′d′]‐s‐indaceno[1, 2b:5, 6b']dithiophene (IT‐4F) cells, respectively) and thermal stabilities. Moreover, a simple yet robust dialysis treatment was proposed to solve the issue of noncontinuity and retain the secondary doping's advantages of quinoid structure simultaneously, thus demonstrating a significant enhancement in device performance. This study will be of great importance to the future exploration of the next generation of post‐treatment strategy. Abstract : Dialysis for solar cells : A simple yet robust dialysis technology is proposed to address the strengths and weaknesses of the classical secondary doping post‐treatment. After secondary doping and dialysis de‐doping processing in order, the PEDOT : PSS hole transport material achieves outstanding application performance in PBDB‐T : ITIC [power conversion efficiency (PCE) 11.82 %] and PM6 : IT‐4F organic solar cells (PCE 14.28 %), which are among the highest values so far.